Chloroplast Ultrastructure and Photosynthetic Response of the Dinoflagellate Akashiwo sanguinea Throughout Infection by Amoebophrya sp. - Chen, Tiantian; Liu, Yun; Hu, Zhangxi; Song, Shuqun; Li, Caiwen (Frontiers in Marine Science, 2021)
The endoparasitic dinoflagellate Amoebophrya infects a number of marine dinoflagellates, including toxic and harmful algal bloom-forming species. The parasite kills its host and has been proposed to be a determining factor in the demise of dinoflagellate blooms in restricted coastal waters. Previous studies have mainly focused on the occurrence, prevalence, and diversity of Amoebophrya, while the interactions between the parasite and its host have received limited attention. Herein, an Amoebophrya sp.-Akashiwo sanguinea co-culture was established from Chinese coastal waters, and morphological, physiological, and transcriptional changes throughout an infection cycle of the parasite were systemically studied. The parasitic dinoflagellate was very infectious, resulting in an infection rate up to 85.83% at a dinospore:host ratio of 10:1. Infected host cells died eventually and released approximately 370 dinospores/cell. The host nuclear structures were rapidly degraded by Amoebophrya infection, and the chloroplasts of parasitized host cells remained intact until the parasite filled the almost entire cell structure. Nevertheless, infected cultures showed sustained but lower levels of photosynthetic performance (∼64% of control cultures), and the photosynthesis-related genes were significantly down-regulated. These findings provide a better understanding of the biological basis of the complex parasite-host interactions, which will be helpful to further elucidate the ecological significance of parasitic dinoflagellates in marine ecosystems.